2010
DOI: 10.1111/j.1472-765x.2010.02922.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of polyacetylenic acids from Prunella vulgaris on various plant pathogens

Abstract: Aims:  This study is aiming at characterizing antifungal substances from the methanol extract of Prunella vulgaris and at investigating those substances’ antifungal and antioomycete activities against various plant pathogens. Methods and Results:  Two polyacetylenic acids were isolated from P. vulgaris as active principles and identified as octadeca‐9,11,13‐triynoic acid and trans‐octadec‐13‐ene‐9,11‐diynoic acid. These two compounds inhibited the growth of Magnaporthe oryzae, Rhizoctonia solani, Phytophthora … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 12 publications
3
10
0
Order By: Relevance
“…lilacina [27], and our research confirmed that this fraction indeed contained lipophilic compounds such as hexadecanoic acid, ethyl palmitate, and ( Z , Z , Z )-ethyl ester-9,12,15-octadecatrienoic acid. It is well known that polyacetylenic acids have a therapeutic potential as antifungals and anti-oomycetes [27] while hexadecanoic acid, as an anti-inflammatory agent, has shown significant inhibitory activity against phospholipase A2 [28]. These reports are consistent with our results suggesting either that very potent unidentified anti-inflammatory compounds may be present in the hexane fraction of P. vulgaris var.…”
Section: Resultssupporting
confidence: 77%
“…lilacina [27], and our research confirmed that this fraction indeed contained lipophilic compounds such as hexadecanoic acid, ethyl palmitate, and ( Z , Z , Z )-ethyl ester-9,12,15-octadecatrienoic acid. It is well known that polyacetylenic acids have a therapeutic potential as antifungals and anti-oomycetes [27] while hexadecanoic acid, as an anti-inflammatory agent, has shown significant inhibitory activity against phospholipase A2 [28]. These reports are consistent with our results suggesting either that very potent unidentified anti-inflammatory compounds may be present in the hexane fraction of P. vulgaris var.…”
Section: Resultssupporting
confidence: 77%
“…Polygala senega L. Polygalaceae Seneca snakeroot snakebite root [15] Root: triterpenoid saponin senegin-II [376] Root: triterpenoid saponins (senegin III, senegin IV) [377] Root: oligosaccharide esters (senegose A, senegose B, senegose C, senegose D, senegose E) [378] Root: oligosaccharide esters (senegose F, senegose G, senegose H, senegose I) [379] Root: oligosaccharide esters (senegose J, senegose K, senegose L, senegoseM, senegose N, senegose O) [380] [15] Plant: lignan aviculin; flavonoids (juglanin, avicularin, astragalin, and betmidin) [384] Plant: naphthoquinone 6-methoxyplumbagin, also β-sitosterol, oleanolic acid, and 5,6,7,4 -tetramethoxyflavanone [385] Aerial parts: flavonoids (avicularin, liquiritin, cinaroside) [386] Plant Leaves: drimane sesquiterpenoids (polygonic acid, 11-ethoxycinnamolide, polygodial acetal, valdiviolide, and fuegin), drimane norsesquiterpenoids (isopolygonal and polygonone) [393] Leaves: flavonoids (7,4 -dimethylquercetin, 3 -methylquercetin, quercetin, isoquercitrin) [394] Leaves: flavonoid sulfates (quercetin 3-sulfate, isorhamnetin 3,7-disulfate, and tamarixetin 3-glucoside-7-sulfate) [395] Leaves Sprout: drimane sesquiterpenoids (polygodial, warburganal) [397] Sprout: flavonoid (2R,3R)-(+)-taxifolin (showed tyrosinase inhibition) [398] Aerial parts: sucrose cinnamyl esters (hydropiperoside A, hydropiperoside B, vanicoside A, vanicoside B, vanicoside E) [399] Sprout: essential oil [β-caryophyllene (9.3%), α-humulene (6.0%), Leaf EO: selin-1 1-en-4α-ol (14.9%), cis-eudesma-6,11-diene (9.4%), 1,10-di-epi-cubenol (8.0%), spathulenol (5.8%) and germacrene D (5.1%) [402] Leaf EO: aromadendrene (55.4%), cucumber alcohol (8.5%) and phytol (5.1%) [403] Aerial parts: rosmarinic acid, ursolic acid, oleanolic acid [404] Aerial parts: rosmarinic acid, ursolic acid, oleanolic acid [405] Aerial parts: four triterpenes, i.e., betulinic acid, ursolic acid, 2α,3α-dihydroxyurs-12-en-28-oic acid, and 2α-hydroxyursolic acid [406] Aerial parts: polyacetylenic acids (octadeca-9,11,13-triynoic acid and trans-octadec-13-ene-9,11-diynoic acid [407] oleanane Aerial parts: polyphenolics (butyl rosmarinate, ethyl rosmarinate, methyl rosmarinate, rosmarinic acid, 3,4,α-trihydroxy-methyl phenylpropionate, and p-coumaric acid) [410] Aerial parts: phenolics (quercetin, rutin, rosmarinic acid, caffeic acid, chlorogenic ac...…”
Section: Asteraceaementioning
confidence: 99%
“…Similarly, Bokhari et al [36] who revealed that GC-MS analysis of crude ethanol extract of C. colocynthis contained the major components Eicosanoic acid, 2-Heptadecenal and l-(+)-Ascorbic acid 2, 6-dihexadecanoate, were responsible for antifungal efficacy. Moreover, Yoon et al [37] reported that Octadeca-9,11,13triynoic acid and trans-octadec-13-ene-9,11-diynoic acid exhibited colony growth inhibition of selected phytopathogenic fungi. These fatty acids can be used as alternative methods for integrated management of phytopathogenic microbes.…”
Section: Quantitative Phytochemical Determination Using Gc-msmentioning
confidence: 99%